The effect of drainage on CO2, CH4 and N2O emissions in the Zoige peatland: a 40-month in situ study - R. Cao; Y. Chen; X. Wu; Q. Zhou; S. Sun (Mires and Peat, 2018)
The Zoige peatland on the Qinghai-Tibet Plateau, the largest alpine peatland in the world, is currently experiencing unprecedented water stress due to climate change and human activities. However, the consequences for emissions of greenhouse gases have not been well studied. We conducted a 40-month in situ field experiment (including deep, shallow and control water table treatments) to examine the effect of drainage on greenhouse gas emissions (CO2, CH4 and N2O). The results showed that drainage significantly increased the emission rates and the total cumulative emissions of CO2 (i.e., ecosystem respiration) and N2O, and reduced CH4 emissions. However, under drained conditions, the cumulative emissions of CO2 and N2O increased significantly during the growing season (May to September) only, whereas the cumulative emissions of CH4 decreased significantly during both the growing season and the non-growing season (October to April). In addition, drainage significantly increased the biomass of aerobic bacteria and methanotrophs. These results indicate that emissions of greenhouse gases in the Zoige peatland are sensitive to short-term drainage and that future studies should consider the response of greenhouse gas fluxes to environmental changes in the non-growing season.